2020
DOI: 10.1136/annrheumdis-2020-eular.4296
|View full text |Cite
|
Sign up to set email alerts
|

Fri0015 phenotype and Function of the Peripheral Blood Dendritic Cells of Psoriasis Patients With and Without Arthritis

Abstract: Background:Psoriasis is a frequent skin disease that can appear with an arthritic manifestation in approximately 30% of the cases [1]. The underlying excessive immune reaction caused by pro-inflammatory cytokines can be triggered by several risk factors [2]. Various subgroups of Dendritic cells (DCs) in the skin play a crucial role in the induction of the dermal inflammatory response [3].Objectives:As the role of peripheral blood DCs remains unknown and the cause of an arthritic manifestation is still not comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, in models of psoriasis, no role for CD197 (CCR7)+ monocytes/monocyte-derived dendritic cells was found in the disease process [13]. Noteworthy are the findings by Schnitte et al, who found that peripheral blood monocyte-derived dendritic cells from PsA patients migrated less towards a MIP3b gradient (CCR7 ligand) than did cells from Pso patients while the level of expression of CD197 (CCR7) was comparable [14]. They did not report if a difference in numbers of CD197 (CCR7)+ monocytes/monocyte-like cells was researched.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, in models of psoriasis, no role for CD197 (CCR7)+ monocytes/monocyte-derived dendritic cells was found in the disease process [13]. Noteworthy are the findings by Schnitte et al, who found that peripheral blood monocyte-derived dendritic cells from PsA patients migrated less towards a MIP3b gradient (CCR7 ligand) than did cells from Pso patients while the level of expression of CD197 (CCR7) was comparable [14]. They did not report if a difference in numbers of CD197 (CCR7)+ monocytes/monocyte-like cells was researched.…”
Section: Discussionmentioning
confidence: 98%